Long-term outcome of magnetic resonance spectroscopic image–directed dose escalation for prostate brachytherapy - King, Martin T. (Brachytherapy, 2016)
PURPOSE: To report the long-term control and toxicity outcomes of patients with clinically localized prostate cancer, who underwent low-dose-rate prostate brachytherapy with magnetic resonance spectroscopic image (MRSI)–directed dose escalation to intraprostatic regions. METHODS AND MATERIALS: Forty-seven consecutive patients between May 2000 and December 2003 were analyzed retrospectively. Each patient underwent a preprocedural MRSI, and MRS-positive voxels suspicious for malignancy were identified. Intraoperative planning was used to determine the optimal seed distribution to deliver a standard prescription dose to the entire prostate, while escalating the dose to MRS-positive voxels to 150% of prescription. Each patient underwent transperineal implantation of radioactive seeds followed by same-day CT for postimplant dosimetry. RESULTS: The median prostate D(90) (minimum dose received by 90% of the prostate) was 125.7% (interquartile range [IQR], 110.3–136.5%) of prescription. The median value for the MRS-positive mean dose was 229.9% (IQR, 200.0–251.9%). Median urethra D(30) and rectal D(30) values were 142.2% (137.5–168.2%) and 56.1% (40.1–63.4%), respectively. Median followup was 86.4 months (IQR, 49.8–117.6). The 10-year actuarial prostate-specific antigen relapse–free survival was 98% (95% confidence interval, 93–100%). Five patients (11%) experienced late Grade 3 urinary toxicity (e.g., urethral stricture), which improved after operative intervention. Four of these patients had dose-escalated voxels less than 1.0 cm from the urethra. CONCLUSIONS: Low-dose-rate brachytherapy with MRSI-directed dose escalation to suspicious intraprostatic regions exhibits excellent long-term biochemical control. Patients with dose-escalated voxels close to the urethra were at higher risk of late urinary stricture.